Le risque tsunami en Nouvelle-Calédonie : Évolutions des facteurs de vulnérabilités et de résiliences à Lifou en territoire coutumier kanak - Matthieu Le Duff; Pascal Dumas; Catherine Sabinot; Michel Allenbach (VertigO)
The last tsunami which has had an impact on the New Caledonia came in March 1875. The south of the Lifou island (Loyalty island) has been most concerned. The tribes of Luengoni Joj, Mu and Ahmelewedr (District of Lösi) focuses the damage and victims of the disaster. If we know the dynamics of seismic and tsunami hazards in New Caledonia, there is no study has yet been interested by conditions of achievements of this disaster (1875), that means, the internal vulnerability factors which explain the disaster. If the hazard comes from of a natural origin, the establishment and structuring of the tribe in this space are produced by social interactions, politics and culture which have to been considered in a historical dimension. The radical choice of moving the tribe of Mu is particularly interesting to analyze from the view of the population resilience. In the same way the relationship between risk and territory is essential to consider here because the socio-spatial organization that we know today is partly inherited from this episode. This paper had two objectives : firstly, to understand the New Caledonia’s tsunami risk situation, on the other, suggest ways of development for an integrated tsunami risk management, based on the concepts of vulnerability and resilience and by this way adapted to the local cultural context and able to respond of human challenges posed by this natural hazard.